ANALISA TARIF LRT JABODEBEK LINTAS BEKASI TIMUR – DUKUH ATAS BERDASARKAN ABILITY TO PAY DAN WILLINGNESS TO PAY - Hendy Bangkit Sanjaya Putra; Sri Yuniarti; Sri Widayatie (FTSP Universitas Jayabaya, 2022)
The Jabodetabek KRL has become the transportation commonly used by commuter users, especially in the Jakarta - Bogor - Depok - Tangerang - Bekasi area and its surroundings. From year to year the KRL fare also continues to change. However, currently the Rp. 3,000 KRL fare is considered sufficient for KRL users and it is proven by the very high public interest in this KRL. Currently, the plan is to build an LRT across the East Bekasi – Dukuh Atas route as another option for transportation, so new fares need to be studied and determined according to the ability and willingness of the community, especially Jabodetabek KRL users. The type of research conducted was quantitative descriptive research with the aim of describing the characteristics of the respondents, the amount of the ATP value, and the magnitude of the WTP value for users of Jabodebek LRT transportation services which was carried out to users of Jabodetabek KRLtransportation services. The data obtained is the result of a survey by distributing question forms to 100 respondents and the existing data collected. As well as processing the data that has been obtained is calculated using the Household budget method regarding the calculation of ATP and WTP. And BOKA is calculated according to the standards on the Jabodetabek KRL. Based on the results of the study, the community's ATP value was Rp. 8,027.00 and the community's WTP was Rp. 7,280.00. The tariff that is used as a reference in the calculation is the tariff formula based on the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 64 of 2016 which is IDR 17,353.00. And the ideal rate for operation is taken from the ATP value, which isIDR 8,027.00. If based on the results of the analysis carried out, it is necessary to provide subsidies in the operation of the Jabodebek LRT.